Congresso Nacional e MERCOSUL: o caso da Aprovação da Entrada da Venezuela - Feliu, Pedro (Meridiano 47 - Journal of Global Studies, 2017)
This paper analyses the roll call vote in National Congress of Brazil on the approval of Venezuela's entry to MERCOSUR. We argue the relevance of the dichotomy between government and opposition as explanatory factor of the votes of legislators on this issue. We outlined the main substantive subject of polarization between both sides.